Meningkatkan Keterampilan Korespondensi Digital dan Komunikasi Siswa: Program Pengabdian Masyarakat di SMA Katolik St. Louis 2 Surabaya - Sulindra, Eric; Sarbani, Yohanes Adven; Cendra, Anastasia Nelladia; Hadisoebroto, Andreas Emmanuel; Hartani, Tuti; Subandoro, Phillipus Suryo; Lestari, Indriana (Journal of Applied Community Engagement, 2024)
Communication and correspondence skills in the digital space are crucial in the digital era. Professional communication via email and other digital media has become an integral part of academic life and the workplace. Therefore, the Office Administration Program at the Faculty of Business, Widya Mandala Catholic University Surabaya, in collaboration with St. Louis 2 Catholic High School, organized a Community Service Program (Abdimas) to enhance students' digital correspondence skills and communication ethics. In this program, students were taught how to create and manage emails professionally, including writing emails with proper structure, using appropriate language, and applying communication ethics. Additionally, the training emphasized the importance of communication ethics, both oral and written, such as polite telephone etiquette, handling formal correspondence, and understanding the norms of professional communication. The results of this training showed that students gained a better understanding of the significance of professional digital communication, which will help them in pursuing further education or entering the workforce.